Informe de resultados del estudio de opinión sociopolítica : abril 2021 - Alfaro Redondo, Ronald; Guzmán Castillo, Jesús 1989-; Sáenz Bonilla, Juan Pablo 1989-; Camacho Sánchez, Sharon Mariela 1995-; Chinchilla, Vianca; Ruiz Tijerino, María de Fátima 1994- (Centro de Investigacion y Estudios Politicos, 2021)
Este informe publicado el 05 de mayo de 2021